(untitled) (Journal of Parents and Teachers, 2025)
This time, Joaquín is not answering questions. The questions are directed at the reader through specific situations involving children and teenagers. It is a game in which parents are presented with these situations and asked to give their first response. For example, what would be your first reaction if your 13-year-old son told you that he no longer wants to study and wants you to help him find a job? Or, how would you react if your 17-year-old daughter suddenly told you that in a few months she will be joining a religious congregation? What if your daughter told you she needed money to help her 18-year-old friend who wants to have an abortion? These are important situations to consider, just in case they arise!